Analysis of the Influence of the Degree of Fiscal Decentralization, Balancing Funds, and Economic Growth on the Islamic Human Development Index (I-HDI) in 8 Provinces in Indonesia - Pramono, Sigit -; Kanafi, Imam; Adinugraha, Hendri Hermawan; Andrean, Rizky (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2025)
This study aims to analyse the influence of the degree of fiscal decentralization, balancing funds, and economic growth on the Islamic Human Development Index (I-HDI) in eight provinces in Indonesia with the lowest I-HDI scores. To fill the research gap, these provinces were categorised based on I-HDI intervals. This study contributes in addressing empirical gaps by focusing on the regions that have received limited attention in the context of Islam-based human development, as well as substantive gaps by integrating variables of fiscal decentralization and balancing funds that have rarely been directly examined in relation to the I-HDI. Methodologically, the System Generalised Method of Moments (System-GMM) approach is applied to address potential endogeneity and the dynamic nature of panel data. A region’s capacity to finance public expenditure is reflected in the degree of fiscal decentralization, while balancing funds serves as the main source for financing public welfare. Although economic growth is generally expected in enhancing welfare, it may exacerbate social inequality if not accompanied by inclusive policies and equitable distribution. The results of this study indicate that the degree of fiscal decentralization has no significant effect on I-HDI in either the short or long term. Conversely, balancing funds has a significantly negative impact, reflecting allocative inefficiency. Economic growth also negatively affects the I-HDI across both time horizons, indicating that its benefits are not evenly distributed. These findings emphasise the need for comprehensive policy evaluation to improve resource allocation efficiency and promote equitable and sustainable human development in line with the principles of Maqasid al-Shariah (Sharia principles).